دور لجان مراجعة الحسابات في تفعيل مبادئ حوكمة الشركات - ميرة, محمد الامين; عزة, الازهر (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الدراسة إلى تحليل ومناقشة دور لجان المراجعة في تفعيل مبادئ حوكمة الشركات والتي تعد في غاية الأهمية نظرا لاتجاه أغلب الشركات إلى تكوين لجان مراجعة الحسابات ولاعتبار حوكمة الشركات هدفا رئيسيا تسعى جميع الشركات لتحقيقه. ولتوضيح الدور تم الاعتماد على المنهج التحليلي الوصفي، حيث تم التوصل إلى أن للجان مراجعة الحسابات دورا بارزا في تفعيل حوكمة الشركات لأنها تعمل على زيادة القدرة الرقابية للآليات التي ترتكز عليها الحوكمة من أجل التطبيق السليم للمبادئ عمليا، كما تقوم بالعديد من المهام التي من شأنها أن تؤدي إلى تعزيز الثقة والمصداقية في التقارير المالية. The purpose of this study is to analyze and discuss the role of audit committees, in activation the principles of corporate governance. Which is very important, given the direction of most companies to the composition of the audit committees. And corporate governance as a key objective of all companies seeking to achieve it. And to illustrate this role, we have adopted an approach descriptive analytic, where it has been proven that audit committees play an important role in the activation of the governance of the company, because they increase the monitoring capacity of the mechanisms that underlie the governance for the proper application of the principles in practice, as are many of the tasks that would lead to the strengthening of confidence and credibility in the financial reports.
مقال
Keywords: حوكمة الشركات، لجان مراجعة الحسابات، مجلس الإدارة، المراجعة الداخلية، المراجعة الخارجية.; corporate governance, audit committees, the board of directors, internal audit, external audit.